The impact of smoking on the morphofunctional state of periodontal tissues of young organism - Romaniuk, A.; Nazaryan, R.; Zakut, Y.; Popova, T.; Gargin, Vitaliy (Kharkiv National Medical University, 2021)
Background. The interrelation of disorders in periodontal tissues with metabolic changes caused, in particular, by a violation of microcirculation, observed namely in smoking but the fact that the effect of smoking on the condition of periodontal tissues at a young age has been studied less than other risk factors deserves special attention. The aim of our study was to experimentally assess the effect of smoking on the morphofunctional state of periodontal tissues in young animals. Materials and methods. Simulation of smoking has been performed with ten-week-old WAG rats using the Boyarchuck chamber. Morphometric studies were performed in the gingival zone which was chosen for morphological interpretation of volumes of specific vascular density in microcirculatory bed, specific density of connective tissue in lamina propria and specific area of tissue with ischemia. The obtained digital data were processed by the methods of variation statistics. Results. Simulation of smoking for four weeks in experimental animals leads to pathological changes in the morphofunctional state of the periodontium with reducing vascular density from 19,44±1,97% to 11,03±1,38 %, increasing area of connective tissue from 18,33±2,71% to 26,49±1,24%, spreading area of tissue with ischemia from 1,14±0,70% to 6,35±1,67%. Conclusions. Morphofunctional changes in the periodontium with damage to the structure of the epithelial membrane and changes in its permeability, microcirculatory disorders, sclerotic changes are a manifestationof the initial inflammatory and dystrophic processes that can lead to persistent chronic pathology.
Keywords: smoking; oral mucosa; ischemia; microcirculatory bed; periodontitis; histology; experiment